Increasing Vitamin D Deficiency among Adults - Chandran, Rabindran; Gedam, D. Sharad (International Journal of Medical Research and Review, 2015)
Vitamin D Deficiency has become prevalent entity know. It is associated with various morbidities like osteoporosis, hip fracture, femur fracture. Early manifestation include pain in weight-bearing joints, back, thighs and/or calves, difficulty in walking and/or climbing stairs, or running and muscle cramps.